2005
DOI: 10.1002/ldr.647
|View full text |Cite
|
Sign up to set email alerts
|

Erodibility in relation to water-dispersible clay for some soils of eastern Nigeria

Abstract: Water dispersible clay (WDC) can influence soil erosion by water. Therefore, in highly erodible soils such as the ones in eastern Nigeria, there is a need to monitor the clay dispersion characteristics to direct and modify soil conservation strategies. Twentyfive soil samples (0-20 cm in depth) varying in texture, chemical properties and mineralogy were collected from various locations in central eastern Nigeria. The objective was to determine the WDC of the soils and relate this to selected soil physical and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
55
0
4

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(64 citation statements)
references
References 21 publications
5
55
0
4
Order By: Relevance
“…Wakindiki et al (2009) asserted that the stability of microaggregates as opposed to their dispersion is important in keeping soil erosion in check. In another study, Igwe (2005) showed that soils which had high dispersible clay were highly prone to hardsetting and subsequently soil erosion. Earlier, Igwe et al (1995) studied the use of some soil aggregate indices to assess potential soil loss in soils of southeastern Nigeria.…”
Section: Microorganismsmentioning
confidence: 97%
See 1 more Smart Citation
“…Wakindiki et al (2009) asserted that the stability of microaggregates as opposed to their dispersion is important in keeping soil erosion in check. In another study, Igwe (2005) showed that soils which had high dispersible clay were highly prone to hardsetting and subsequently soil erosion. Earlier, Igwe et al (1995) studied the use of some soil aggregate indices to assess potential soil loss in soils of southeastern Nigeria.…”
Section: Microorganismsmentioning
confidence: 97%
“…The importance of microaggregates in the processes of infiltration, sealing and crust formation, runoff and soil erosion was also emphasized by Levy and Miller (1997). Some of the indices for microaggregate stability determination include, clay dispersion ratio (CDR), aggregated silt and clay (ASC) (Igwe et al 2009), water dispersible clay (WDC) (Igwe 2005) among others. Rhoton et al (2007) also showed that indices like WDC have been recognized as a key criterion for assessing the risk of surface sealing and crusting, and erosion of soil by water.…”
Section: Microorganismsmentioning
confidence: 98%
“…Soil aggregate stability in water has been described as one of the major factor controlling soils susceptibility to water erosion (Egashlra, Kaetsu, & Takuma, 1983;Igwe, 2005). However, this soil-water interaction is not only dependent of the chemical composition of the soil aggregate, but also on the chemical composition of the prevailing aqueous solution.…”
Section: Introductionmentioning
confidence: 99%
“…(Igwe and Udegbunam, 2008). Igwe (2005) remarked that the clay dispersion ratio and dispersible ratio were found to be good indices for predicting erodibility in some soils of southeastern Nigeria. In another study Igwe et al (1995) observed that DR and CDR correlated very significantly with erodibility in the Universal Soil Loss Equation (USLE) model.…”
Section: Soilsmentioning
confidence: 99%
“…Igwe (2005) remarked that pH, soil organic carbon, exchangeable Ca, exchangeable acidity, cation exchange capacity, sodium adsorption ratio, clay and silt contents of the soil are the soil factors that influence the water dispersible properties of the soils. The objective of this study was to determine the effect of exchangeable Ca and Mg on dispersion, chemical composition of soils from eight locations in Southern Nigeria.…”
Section: Introductionmentioning
confidence: 99%